Negative electrode for lithium-sulfur battery and lithium-sulfur battery containing the same
By forming a graphene protective layer with fewer defects on the surface of the negative electrode current collector of the lithium sulfur battery, the corrosion problem caused by lithium polysulfide is solved, and the life and performance of the lithium sulfur battery is significantly improved.
Patent Information
- Application Number
- CN202180005927.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-21
- Filing Date
- 2021-07-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-07-23
AI Technical Summary
The dissolution of lithium polysulfide in lithium-sulfur batteries leads to loss of positive electrode active materials and corrosion of negative electrode current collectors, affecting battery performance and life. The existing technology has failed to effectively solve the problem of negative electrode performance deterioration.
A graphene protective layer with fewer defects is formed on the surface of the negative electrode current collector of the lithium sulfur battery, and is manufactured by chemical vapor deposition method to prevent lithium polysulfide from contacting the negative electrode current collector and prevent corrosion.
Effectively prevent the corrosion of lithium polysulfide on the negative electrode current collector, improve the capacity and life characteristics of lithium-sulfur batteries, and significantly improve the stability and performance of the battery.
Smart Images

Figure CN114556612B_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0092325 filed on Jul. 24, 2020 and Korean Patent Application No. 10-2021-0095654 filed on Jul. 21, 2021, the entire contents of which are incorporated herein by reference.
[0002] The invention relates to a negative electrode for a lithium-sulfur battery and a lithium-sulfur battery comprising the negative electrode. Background Art
[0003] As the use range of lithium secondary batteries expands not only to portable electronic devices and communication devices but also to electric vehicles (EVs) and electric power storage systems (ESSs), demand for high capacity of lithium secondary batteries used as their power sources has been growing.
[0004] Among various lithium secondary batteries, a lithium-sulfur battery is a battery system that uses a sulfur-based material including an SS bond (sulfur-sulfur bond) as a positive electrode active material and uses lithium metal as a negative electrode active material.
[0005] There are advantages in that sulfur, which is the main material of the positive electrode active material in the lithium-sulfur battery, has a low atomic weight, is very abundant in resources and is thus easy to supply and receive, and is inexpensive, non-toxic, and environmentally friendly.
[0006] In addition, lithium-sulfur batteries have a conversion reaction between lithium ions and sulfur (S8+16Li + +16e - →8Li2S) has a theoretical discharge capacity of 1675mAh / g, and when lithium metal (theoretical capacity: 3860mAh / g) is used as the negative electrode, the theoretical energy density is 2600Wh / kg. Since the energy density of lithium-sulfur batteries is much higher than the theoretical energy density of other battery systems currently under research (Ni-MH battery: 450Wh / kg; Li-FeS battery: 480Wh / kg; Li-MnO2 battery: 1000Wh / kg; Na-S battery: 800Wh / kg) and lithium secondary batteries (250Wh / kg), lithium-sulfur batteries have attracted much attention as lithium secondary batteries with high capacity, environmental friendliness and low cost among the secondary batteries developed so far, and are the next-generation battery system that is undergoing multiple studies.
[0007] Despite these advantages, lithium-sulfur batteries have a problem in that it is difficult to ensure battery performance and operational stability due to lithium polysulfide generated during the charge / discharge process. Specifically, in lithium-sulfur batteries, lithium polysulfide (lithium polysulfide, Li2S x, x = 2 to 8), and some of these substances are easily soluble in the electrolyte. As a result, the positive electrode active material is lost, resulting in a decrease in the electrochemical reactivity of the positive electrode and a decrease in the capacity and life of the battery.
[0008] In particular, lithium polysulfide diffused into the negative electrode through the electrolyte tends to react with the negative electrode active material lithium metal to form insoluble products on the surface, and also reacts with the negative electrode collector to cause damage to the negative electrode collector, negatively affecting the operation of the negative electrode and the performance of the battery.
[0009] Therefore, various techniques have been proposed to solve the problems related to lithium polysulfides in lithium-sulfur batteries.
[0010] For example, Korean Patent Unexamined Publication No. 2017-0139761 discloses that by including a positive electrode active material layer containing a nitrogen-doped carbon material and a protective film, the dissolution of lithium polysulfide can be delayed, thereby improving the capacity and life of the battery.
[0011] In addition, Korean Patent Unexamined Publication No. 2016-0037084 discloses that by coating graphene on a sulfur-containing carbon nanotube aggregate, lithium polysulfide can be prevented from being dissolved.
[0012] These patents improve the performance or life of lithium-sulfur batteries to a certain extent by introducing materials capable of absorbing lithium polysulfide into the positive electrode in the form of a coating to prevent the dissolution of lithium polysulfide and the resulting loss of sulfur. However, the effect is not enough for actual commercial applications.
[0013] In addition, in the case of the prior art, the problem of performance degradation and damage of the negative electrode caused by the dissolution of lithium polysulfide is not considered at all. Therefore, it is necessary to further develop a lithium-sulfur battery that can effectively block lithium polysulfide, thereby improving the capacity characteristics, life characteristics and stability of the negative electrode and showing high capacity characteristics.
[0014] Prior art literature
[0015] Patent Literature
[0016] Korean Patent Unexamined Publication No. 2017-0139761 (December 20, 2017), Cathode for metal-sulfur batteryhaving cathode active material layer containing N-doped carbon and protective film
[0017] Korean Patent Unexamined Publication No. 2016-0037084 (April 5, 2016), Sulfur-carbon nanotube composite material, method of preparing the same, cathode active material for lithium-sulfur battery including the same and lithium-sulfur battery including the same Summary of the invention
[0018] Technical issues
[0019] Therefore, the inventors of the present invention conducted various studies to solve the above-mentioned problems, and as a result, confirmed that when a protective layer containing graphene is formed on the surface of the negative electrode collector, the performance of the lithium-sulfur battery can be improved by preventing damage to the negative electrode collector caused by lithium polysulfide, thereby completing the present invention.
[0020] Therefore, an object of the present invention is to provide a negative electrode for a lithium-sulfur battery, which has excellent corrosion resistance to lithium polysulfide.
[0021] In addition, another object of the present invention is to provide a lithium-sulfur battery comprising the negative electrode.
[0022] Technical Solution
[0023] In order to achieve the above object, the present invention provides a negative electrode for a lithium-sulfur battery, wherein the negative electrode comprises a negative electrode collector and a protective layer located on at least one surface of the negative electrode collector and containing graphene.
[0024] The protective layer may include single-layer graphene or multi-layer graphene.
[0025] The multilayer graphene may have 2 to 100 layers.
[0026] The graphene may have a ratio of a 2D peak to a G peak of 0.2 to 2.0 in a Raman spectrum.
[0027] The graphene may have a ratio of a D peak to a G peak of 0.01 to 0.6 in a Raman spectrum.
[0028] The protective layer may have a thickness of 0.1 nm to 50 nm.
[0029] The protective layer may be impermeable to lithium polysulfide.
[0030] The protective layer may be formed by chemical vapor deposition.
[0031] The negative electrode current collector may include at least one selected from the group consisting of nickel, copper, stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, zinc, molybdenum, tungsten, silver, gold, ruthenium, platinum, iridium, aluminum, tin, bismuth, and antimony.
[0032] The negative electrode current collector may be in the form of a film, a sheet, a foil, a screen, a net, a porous body, a foam, or a non-woven fabric.
[0033] The negative electrode for a lithium-sulfur battery may further include a negative electrode active material layer on the protective layer.
[0034] In addition, the present invention provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the negative electrode for the lithium-sulfur battery.
[0035] Beneficial Effects
[0036] The negative electrode for a lithium-sulfur battery according to the present invention prevents damage to the negative electrode collector caused by lithium polysulfide by providing a protective layer containing graphene with fewer defects on the negative electrode collector to inhibit the infiltration of lithium polysulfide, thereby realizing a lithium-sulfur battery with excellent life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a scanning electron microscope image of the copper current collector according to Example 1 of the present invention.
[0038] Figure 2 is a scanning electron microscope image of the copper current collector according to Comparative Example 1 of the present invention.
[0039] Figure 3 are scanning electron microscope images of the copper current collectors of Examples 1 and 4 after the oxidation degree of copper was measured according to Experimental Example 2 ((a): Example 1; (b): Example 4).
[0040] Figure 4 is a scanning electron microscope image of the copper current collector according to Example 6 of the present invention.
[0041] Figure 5 : is a graph showing the evaluation results of the life characteristics of the coin-type lithium-sulfur batteries according to Examples 2, 5, 7 and 9 and Comparative Examples 2 and 7.
[0042] Figure 6 Graphs showing evaluation results of life characteristics of coin-type lithium-sulfur batteries according to Example 7 and Comparative Examples 2 and 5.
[0043] Figure 7 Graphs showing evaluation results of life characteristics of pouch-type lithium-sulfur batteries according to Example 3 and Comparative Example 3.
[0044] Figure 8 is a scanning electron microscope image of a cross section of the negative electrode of Example 3 after the life characteristics of the battery were evaluated according to Experimental Example 3.
[0045] Fig. 9 is a scanning electron microscope image of a cross section of the negative electrode of Comparative Example 3 after the life characteristics of the battery were evaluated according to Experimental Example 3. DETAILED DESCRIPTION
[0046] Hereinafter, the present invention will be described in more detail.
[0047] The terms and words used in this specification and claims should not be construed as limited to common or dictionary terms, and should be construed as meanings and concepts consistent with the technical idea of the present invention on the basis of the principle that the inventor can appropriately define the concepts of the terms to describe his invention in the best possible manner.
[0048] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular forms "a", "a", "the" and "said" include plural indicators. It should be understood that the terms used in this specification such as "comprising" or "having" are intended to clearly indicate the presence of the described features, numbers, steps, operations, components, parts or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, numbers, steps, operations, components, parts or combinations thereof.
[0049] As used herein, the term "composite material" refers to a material in which two or more materials are combined to exhibit more effective functions while forming physically and chemically different phases from each other.
[0050] As used herein, the term "polysulfide" includes "polysulfide ions (S x 2- , x=8, 6, 4, 2)” and “lithium polysulfide (Li2S x or LiS x - , x=8, 6, 4, 2)” concept.
[0051] Among various secondary batteries, lithium-sulfur batteries have high theoretical discharge capacity and theoretical energy density, and sulfur used as a positive electrode active material has the advantages of being low cost and environmentally friendly due to its abundant reserves, so lithium-sulfur batteries have attracted much attention as next-generation secondary batteries.
[0052] As the lithium-sulfur battery is discharged, sulfur as the positive electrode active material continuously transforms from a cyclic S8 structure to lithium polysulfide (Li2Sx , x = 8, 6, 4, 2) and when the lithium polysulfide is completely reduced, lithium sulfide (Li2S) is finally produced. Among the lithium polysulfides that are intermediate products of this sulfur reduction reaction (discharge), lithium polysulfide (Li2S) with a high sulfur oxidation number is x , usually x>4) is a highly polar substance and is easily dissolved in an electrolyte containing a hydrophilic organic solvent, so there is a problem of lithium polysulfide being released outside the reaction area of the positive electrode.
[0053] This dissolution of lithium polysulfide leads to sulfur loss, which prevents sulfur from participating in the electrochemical reaction. In addition, the dissolved lithium polysulfide reacts with the negative electrode active material lithium to form solid lithium sulfide on the negative electrode surface, and the solid lithium sulfide does not decompose even during charging, so it not only plays the role of irreversible capacity but also interferes with the electrochemical reaction on the negative electrode surface. In addition, because the lithium polysulfide diffused to the negative electrode easily reacts with the copper constituting the negative electrode collector, there is a problem that copper sulfide is formed and the negative electrode collector is corroded and becomes porous. Therefore, because the diffusion of lithium polysulfide causes structural damage and loss of active materials at the positive and negative electrodes, the deterioration of the capacity and life characteristics of the lithium-sulfur battery is accelerated, and therefore, in actual operation, all theoretical capacities and energy densities cannot be achieved.
[0054] To this end, in the prior art, the following methods have been proposed: a method of introducing a material capable of inhibiting the dissolution of lithium polysulfide into the positive electrode or separator in the form of an additive or a coating; or a method of changing the composition of the electrolyte. However, there are disadvantages in that the effect of improving the dissolution of lithium polysulfide is not obvious, and the sulfur loading is limited, and it has serious problems in battery stability or low efficiency in process. In addition, in the case of the prior art, the problem of damage to the negative electrode, especially the negative electrode collector, caused by lithium polysulfide is not discussed.
[0055] Therefore, in order to improve the problem of lithium-sulfur battery degradation caused by corrosion of the negative electrode collector by lithium polysulfide, the present invention provides a negative electrode for a lithium-sulfur battery having a protective layer, which prevents the contact between lithium polysulfide and the negative electrode collector without interfering with the electron movement between the negative electrode collector and the negative electrode active material.
[0056] Specifically, the negative electrode for a lithium-sulfur battery according to the present invention includes a negative electrode current collector and a protective layer located on at least one surface of the negative electrode current collector and including graphene.
[0057] In the present invention, the negative electrode current collector supports the negative electrode active material and supplies electrons provided from the external conductor to the negative electrode active material, or conversely, plays a role of collecting electrons generated by an electrode reaction and transferring them to the external conductor.
[0058] There is no particular limitation on the negative electrode current collector as long as it has high electronic conductivity without causing chemical changes in the lithium-sulfur battery. For example, the negative electrode current collector may include at least one selected from the following: nickel (Ni), copper (Cu), stainless steel (SUS), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), zinc (Zn), molybdenum (Mo), tungsten (W), silver (Ag), gold (Au), ruthenium (Ru), platinum (Pt), iridium (Ir), aluminum (Al), tin (Sn), bismuth (Bi) and antimony (Sb). Preferably, the negative electrode current collector may include copper.
[0059] The negative electrode current collector may have a fine concavoconvex structure on its surface or adopt a three-dimensional porous structure to increase the binding force with the negative electrode active material. Therefore, the negative electrode current collector may be in the form of a film, sheet, foil, screen, mesh, porous body, foam or non-woven fabric.
[0060] In the present invention, the negative electrode current collector includes a protective layer formed on at least one face thereof and containing graphene.
[0061] Graphene is a substance in which a plurality of carbon atoms are covalently linked to each other to form a polycyclic aromatic molecule and thereby form a layer or sheet. Since such graphene has excellent chemical and thermal stability and high electron conductivity and is impermeable to lithium polysulfide, the negative electrode collector can be prevented from contacting with lithium polysulfide by forming a protective layer containing graphene on the surface of the negative electrode collector. Therefore, by solving the problem of corrosion of the negative electrode collector caused by the dissolution of lithium polysulfide in conventional lithium-sulfur batteries or the problem of making the negative electrode collector porous, the capacity and life characteristics of lithium-sulfur batteries can be improved.
[0062] It is preferred that the graphene-containing protective layer exists between the negative electrode current collector and the negative electrode active material described later, and has sufficient conductivity without preventing the movement of electrons therebetween.
[0063] The graphene-containing protective layer can be manufactured by various methods such as mechanical exfoliation, epitaxial chemical exfoliation, chemical vapor deposition (CVD), etc. Preferably, chemical vapor deposition is used to form a protective layer containing graphene with good quality.
[0064] Typically, in the manufacturing process of graphene, a carbon core is produced and grows around it. As the graphene grains growing around the core meet each other, grain boundaries are formed. In each grain, the arrangement does not match, and the grain boundary acts as a defect. It is known that the boundary between the grains is a factor that reduces the charge transfer performance, and these defects in graphene promote the reaction with the surrounding environment, resulting in a weakening of oxidation resistance (corrosion resistance). In addition, it can be seen that the specific resistance when passing through the grain boundary increases by 2 to 10 times more than the specific resistance of the grain, and the grain boundary becomes a defect.
[0065] In addition, carbon atoms connected by covalent bonds constituting graphene grown at any point on the substrate form 6-membered ring grains as a basic repeating unit. However, if the growth direction of the graphene grains is different, the individual grains collide and cannot maintain the 6-membered ring structure, and form 5-membered rings or 7-membered rings, resulting in irregular crystal arrangement, and this irregularity can act as a defect that reduces the oxidation resistance of graphene.
[0066] Therefore, if the above-mentioned defects exist in graphene, since it acts as a corrosion point by enabling lithium polysulfide, specifically polysulfide ions, to move in the vertical direction in graphene, thereby causing corrosion of the negative electrode collector, the protective layer according to the present invention preferably contains graphene with the least defects.
[0067] As described above, the large size of the graphene grains and the number of grains having a 6-membered ring structure mean that the number of defects in the graphene is very small, thereby being able to maintain the original physical properties of the graphene. Therefore, the protective layer according to the present invention contains graphene with very few defects caused by grain boundaries, i.e., having large grains and a 6-membered ring structure.
[0068] The degree of defects in graphene can be confirmed by Raman spectroscopy. Raman spectroscopy is usually used to evaluate the properties of graphene, and the number of layers and the degree of defects are determined by the Raman shift of 1350cm -1 The D peak near the Raman shift of 1600cm -1 The G peak near the Raman shift of 2700 cm -1 The position and shape of the peak represented by the nearby 2D peak change. The ratio of the D peak to the G peak (D peak / G peak) is used as a measure for indicating graphene defects, and the lower the ratio, the better the graphene. In addition, the ratio of the 2D peak to the G peak (2D peak / G peak) is used as a measure for indicating the layer of graphene, and shows a higher value when the graphene is a single layer.
[0069] As a result of Raman spectroscopy analysis of the graphene contained in the protective layer of the present invention, the ratio of the 2D peak to the G peak in the Raman spectrum is 0.2 to 2.0, and the ratio of the D peak to the G peak is 0.01 to 0.6. Thus, it can be confirmed that the protective layer according to the present invention contains graphene with fewer defects. Preferably, the ratio of the 2D peak to the G peak in the Raman spectrum of the protective layer is 0.2 to 1.7, and the ratio of the D peak to the G peak is 0.01 to 0.4. More preferably, the ratio of the 2D peak to the G peak in the Raman spectrum of the protective layer is 0.2 to 1.5, and the ratio of the D peak to the G peak is 0.01 to 0.2.
[0070] The graphene-containing protective layer may be formed on one surface or both surfaces of the negative electrode current collector, but is not particularly limited in the present invention.
[0071] The graphene-containing protective layer may include single-layer graphene or multi-layer graphene.
[0072] The multilayer graphene may be a multilayer graphene in which at least two layers, preferably 2 to 100 layers of graphene are stacked. The graphene contained in the protective layer is preferably a single layer of graphene or a multilayer of 2 to 30 layers of graphene.
[0073] There is no particular limitation on the thickness of the protective layer, and there is a range that does not increase the internal resistance of the battery while ensuring the above-mentioned effects. For example, the thickness of the protective layer may be 0.1 to 50 nm, preferably 0.1 to 30 nm. If the thickness of the protective layer is less than the above range, the effect of preventing contact with lithium polysulfide is not obvious, so that it cannot play the role of a protective layer. On the contrary, if the thickness of the protective layer exceeds the above range, the interface resistance may become high, which may cause an increase in the internal resistance during battery operation.
[0074] As described above, when forming the protective layer containing graphene, it is preferable to use chemical vapor deposition because it is possible to form graphene having high electrical conductivity, few defects and a thin thickness.
[0075] For example, the graphene-containing protective layer according to the present invention can be manufactured by heat-treating the negative electrode current collector and forming the graphene-containing protective layer on the heat-treated negative electrode current collector by chemical vapor deposition.
[0076] The heat treatment is carried out in a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and argon at 900°C to 1200°C and 1 torr to 760 torr for 1 to 5 hours to prevent oxidation of the negative electrode collector, wherein preferably, the heat treatment is carried out while injecting hydrogen or a mixed gas of hydrogen and argon at 1 sccm to 100 sccm of hydrogen or 1 sccm to 100 sccm of hydrogen / 10 sccm to 1000 sccm of argon.
[0077] The chemical vapor deposition uses a mixed gas of hydrogen and a carbon-containing gas as a precursor and is carried out at 900° C. to 1200° C. and 0.1 torr to 760 torr for 10 minutes to 3 hours, wherein the mixed gas of hydrogen and the carbon-containing gas is preferably injected at a rate of 1 sccm to 100 sccm of hydrogen / 1 sccm to 100 sccm of carbon-containing gas.
[0078] In this case, the carbon-containing gas may be any one selected from the group consisting of hydrocarbon gas, gaseous hydrocarbon compound, gaseous alcohol having 1 to 6 carbon atoms, carbon monoxide, and a mixture thereof, and in particular, hydrocarbon gas may be preferably used.
[0079] In addition, as the hydrocarbon gas, any one selected from the following: methane, ethane, propane, butane, ethylene, propylene, butene, acetylene, butadiene and mixtures thereof are used, and methane gas, which is easy to handle, is more preferably used. In addition, as the gaseous hydrocarbon compound, any one selected from the following: pentane, hexane, cyclohexane, benzene, toluene, xylene and mixtures thereof can be used, but it is not limited thereto.
[0080] In particular, in the chemical vapor deposition method, the quality of graphene can be improved by taking advantage of the fact that the number of defects in the graphene contained in the protective layer decreases as the injection rate of the precursor decreases. Therefore, in the chemical vapor deposition process, the injection rate of the mixed gas of the precursor hydrogen gas and the carbon-containing gas is more preferably 1 sccm to 50 sccm of hydrogen gas / 1 sccm to 50 sccm of carbon-containing gas, and more preferably 1 sccm to 25 sccm of hydrogen gas / 1 sccm to 25 sccm of carbon-containing gas.
[0081] The negative electrode for a lithium-sulfur battery of the present invention may further include a negative electrode active material layer on the protective layer.
[0082] The negative electrode active material layer may include a negative electrode active material and optionally a conductive material and a binder.
[0083] The negative electrode active material may include: + ) material, a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal, or a lithium alloy.
[0084] Able to reversibly insert or deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0085] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of a lithium metal film or lithium metal powder.
[0086] The conductive material is a material that electrically connects the electrolyte and the negative electrode active material to serve as a path for electrons provided by the negative electrode current collector to move to the negative electrode active material, and the conductive material may be used without limitation as long as it has conductivity.
[0087] For example, as the conductive material, the following substances can be used alone or in combination: carbon black such as Super-P, Deko black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; carbon derivatives such as carbon nanotubes or fullerenes; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; and conductive polymers such as polyaniline, polythiophene, polyacetylene and polypyrrole.
[0088] The binder holds the negative electrode active material in the negative electrode current collector and organically connects the negative electrode active materials to further increase the binding force therebetween, and as the binder, any binder known in the art may be used.
[0089] For example, the adhesive can be any one selected from the following or a mixture or copolymer of two or more thereof: fluororesin adhesives, including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber adhesives, including styrene-butadiene rubber (SBR), nitrile rubber and styrene-isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; polyol adhesives; polyolefin adhesives, including polyethylene and polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.
[0090] There is no particular limitation on the method for forming the negative electrode active material layer, and a method for forming a layer or film commonly used in the art can be used. For example, a method such as compression, coating or deposition can be used. In addition, the negative electrode of the present invention also includes a lithium metal film formed on the metal plate by initial charging after assembling the battery without a lithium film on the negative electrode collector.
[0091] In addition, the present invention provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the negative electrode for the lithium-sulfur battery.
[0092] The lithium-sulfur battery comprises: a positive electrode; a negative electrode; and an electrolyte disposed therebetween, wherein the negative electrode comprises the negative electrode for a lithium-sulfur battery according to the present invention.
[0093] The positive electrode may include a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector.
[0094] The positive electrode may include a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector.
[0095] The positive electrode current collector is used to support the positive electrode active material, and is as described in the negative electrode current collector.
[0096] The positive electrode active material layer contains a positive electrode active material, and may further contain a conductive material, a binder, an additive, and the like.
[0097] The positive electrode active material may include sulfur, specifically, may include at least one selected from the following: elemental sulfur (S8) and a sulfur compound. The positive electrode active material may include at least one selected from the following: inorganic sulfur, Li2S n (n≥1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C2S x ) n , x=2.5 to 50, n≥2). Preferably, the positive electrode active material may be inorganic sulfur.
[0098] Since sulfur contained in the positive electrode active material alone has no conductivity, it is used in combination with a conductive material such as a carbon material. Therefore, sulfur is contained in the form of a sulfur-carbon composite material. Preferably, the positive electrode active material may be a sulfur-carbon composite material.
[0099] The carbon in the sulfur-carbon composite material is a porous carbon material and provides a framework capable of uniformly and stably fixing sulfur, and compensates for the low conductivity of sulfur so that the electrochemical reaction can proceed smoothly.
[0100] Porous carbon materials can generally be manufactured by carbonizing precursors of various carbon materials. The porous carbon material may contain non-uniform pores therein, the average diameter of the pores is in the range of 1 nm to 200 nm, and the porosity may be in the range of 10% to 90% of the total volume of the porous carbon material. If the average diameter of the pores is less than the above range, the pore size is only at the molecular level and impregnation with sulfur is impossible. On the contrary, if the average diameter of the pores exceeds the above range, the mechanical strength of the porous carbon material is weakened, which is not preferred for the manufacturing process applied to the electrode.
[0101] The shape of the porous carbon material is in the form of spheres, rods, needles, plates, tubes, or blocks, and can be used without limitation as long as it is generally used in lithium-sulfur batteries.
[0102] The porous carbon material may have a porous structure or a high specific surface area, and may be any one of the porous carbon materials conventionally used in the art. For example, the porous carbon material may be, but is not limited to, at least one selected from the following: graphite; graphene; carbon black such as Deco black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); graphites such as natural graphite, artificial graphite, and expanded graphite; and activated carbon. Preferably, the porous carbon material may be a carbon nanotube.
[0103] Relative to 100 parts by weight of the sulfur-carbon composite material, the content of sulfur in the sulfur-carbon composite material can be 60 parts by weight to 90 parts by weight, preferably 65 parts by weight to 85 parts by weight, and more preferably 70 parts by weight to 80 parts by weight. If the content of sulfur is lower than the above range, as the content of porous carbon material in the sulfur-carbon composite material increases relatively, the specific surface area increases, thereby increasing the content of the binder during the manufacture of the positive electrode. This increase in the amount of binder will eventually increase the sheet resistance of the positive electrode and act as an insulator to prevent electrons from passing through, thereby degrading the performance of the battery. On the contrary, if the content of sulfur exceeds the above range, the sulfur that is not combined with the porous carbon material aggregates with each other or dissolves again to the surface of the porous carbon material, thereby becoming difficult to receive electrons and cannot participate in the electrochemical reaction, resulting in a loss of battery capacity.
[0104] In addition, the sulfur in the sulfur-carbon composite material is located on at least one of the inner and outer surfaces of the above-mentioned porous carbon material, and at this time, the sulfur may be present in an area of less than 100%, preferably 1% to 95%, and more preferably 60% to 90% of the entire inner and outer surfaces of the porous carbon material. When sulfur is present on the inner and outer surfaces of the porous carbon material within the above range, it can exhibit a maximized effect in terms of electron transport area and wettability with the electrolyte. Specifically, because sulfur is thinly and uniformly infiltrated on the inner and outer surfaces of the porous carbon material within the above range, the electron migration contact area can be increased during the charge / discharge process. If sulfur is located in 100% of the area of the entire inner and outer surfaces of the porous carbon material, the carbon material is completely covered with sulfur, resulting in poor wettability to the electrolyte and poor contact with the conductive material contained in the electrode, so that it cannot receive electrons and cannot participate in the electrochemical reaction.
[0105] The present invention has no particular limitation on the method for preparing the sulfur-carbon composite material, and a method commonly used in the art can be used. For example, a method of simply mixing sulfur and porous carbon material and then heat-treating them to form a composite material can be used.
[0106] In addition to the above components, the positive electrode active material may further include at least one additive selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of these elements with sulfur.
[0107] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., and the IIIA group elements may include Al, Ga, In, Tl, etc., and the IVA group elements may include Ge, Sn, Pb, etc.
[0108] The content of the positive electrode active material may be 40% to 95% by weight, preferably 45% to 90% by weight, and more preferably 60% to 90% by weight, relative to a total of 100% by weight of the positive electrode active material layer constituting the positive electrode. If the content of the positive electrode active material is lower than the above range, it is difficult for the positive electrode to fully exert the electrochemical reaction. On the contrary, if the content exceeds the above range, the problem is that the resistance of the positive electrode increases and the physical properties of the positive electrode decrease due to the relatively insufficient content of the conductive material and the binder described later.
[0109] The positive electrode active material layer may also optionally contain a conductive material that allows electrons to move smoothly in the positive electrode (specifically, the positive electrode active material), and a binder for well attaching the positive electrode active material to the current collector. At this time, the conductive material and the binder are as described above.
[0110] In the present invention, there is no particular limitation on the method of manufacturing the positive electrode, and a method known to those skilled in the art or various methods improved therefrom may be used.
[0111] For example, the positive electrode may be prepared by preparing a positive electrode slurry composition including the above components and then applying the positive electrode slurry composition to at least one surface of a positive electrode current collector.
[0112] The positive electrode slurry composition includes the positive electrode active material, the conductive material, and the binder as described above, and may further include a solvent in addition to these.
[0113] As a solvent, a solvent capable of uniformly dispersing the positive electrode active material, the conductive material and the binder is used. As such a solvent, water is most preferably used as an aqueous solvent, but it is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water can be used. Examples of lower alcohols include methanol, ethanol, propanol, isopropanol and butanol, and preferably, they can be mixed with water for use.
[0114] The content of the solvent may be at a level having a concentration such that coating is facilitated, and the specific content varies depending on the coating method and equipment.
[0115] If necessary, the positive electrode slurry composition may further include materials generally used to improve its function in the relevant technical field. For example, a viscosity modifier, a fluidizer, a filler, etc. are mentioned.
[0116] The present invention has no particular limitation on the method for coating the positive electrode slurry composition, and there can be mentioned, for example, methods such as a doctor blade method, a die casting method, a comma coating method, and a screen printing method. In addition, after forming on a separate substrate, the positive electrode slurry can be coated on the positive electrode collector by a pressing or laminating method.
[0117] After coating, a drying process for removing the solvent may be performed. The drying process is performed at a temperature and time at a level capable of fully removing the solvent, and the conditions may vary depending on the type of solvent, and thus are not particularly limited in the present invention. For example, there may be mentioned: a drying method using warm air, hot air or low-humidity air; a vacuum drying method; and a drying method by irradiating (far) infrared rays or electron beams. The drying speed is adjusted in a manner that allows the solvent to be removed as quickly as possible, within a speed range that does not cause the positive electrode active material layer to rupture due to normal stress concentration or within a speed range that does not cause the positive electrode active material layer to peel off from the positive electrode collector.
[0118] In addition, after drying, the density of the positive electrode active material in the positive electrode can be increased by pressing the current collector. As a pressing method, methods such as molding and calendaring are mentioned.
[0119] The negative electrode is as described above.
[0120] The electrolyte contains lithium ions and serves to cause an electrochemical oxidation or reduction reaction in the positive electrode and the negative electrode.
[0121] The electrolyte may be a non-aqueous electrolyte solution or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte, and contains an electrolyte salt and an organic solvent.
[0122] The electrolyte salt contained in the nonaqueous electrolyte is a lithium salt. The lithium salt can be used without limitation as long as it is a lithium salt commonly used in an electrolyte for a lithium secondary battery. For example, the lithium salt may be LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylate, tetraphenylborate, lithium imide, etc.
[0123] The concentration of the lithium salt can be appropriately determined in consideration of ion conductivity, solubility, etc., and can be, for example, 0.1M to 4.0M, preferably 0.5M to 2.0M. If the concentration of the lithium salt is less than the above range, it is difficult to ensure ion conductivity suitable for driving the battery. On the contrary, if the concentration of the lithium salt exceeds the above range, the viscosity of the electrolyte increases and the mobility of lithium ions is reduced, and the decomposition reaction of the lithium salt itself increases, thereby reducing the performance of the battery. Therefore, the concentration of the lithium salt is appropriately adjusted within the above range.
[0124] As the organic solvent contained in the nonaqueous electrolyte, organic solvents generally used in electrolytes for lithium secondary batteries can be used without limitation, and for example, ethers, esters, amides, linear carbonates, cyclic carbonates and the like can be used alone or in combination of two or more thereof.
[0125] The ether compounds may include acyclic ethers and cyclic ethers.
[0126] For example, the acyclic ether may be, but is not limited to, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.
[0127] For example, the cyclic ether may be, but is not limited to, at least one selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxolane, 1,4-dioxolane, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran ... alkanes, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene and dimethyl isosorbide.
[0128] Examples of esters of the organic solvent may include, but are not limited to, at least one selected from the following or a mixture of two or more thereof: methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone.
[0129] Specific examples of the linear carbonate compound may representatively include, but are not limited to, at least one selected from the following or a mixture of two or more thereof: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methylpropyl carbonate and ethylpropyl carbonate.
[0130] In addition, specific examples of cyclic carbonate compounds may include at least one selected from the following or a mixture of two or more thereof: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate and halides thereof. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC) and the like.
[0131] In addition to the above-mentioned electrolyte salt and organic solvent, the electrolyte may further contain nitric acid or nitrite compounds as additives. The nitric acid or nitrite compounds have the function of forming a stable film on the lithium metal electrode as the negative electrode and improving the charge / discharge efficiency.
[0132] The present invention has no particular limitation on nitric acid or nitrous acid compounds, but can be at least one selected from the following: inorganic nitric acid or nitrous acid compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2); organic nitric acid or nitrous acid compounds such as methyl nitrate, dialkyl imidazole nitrate Guanidine nitrate, imidazole nitrate Pyridine nitrate Ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, preferably lithium nitrate.
[0133] The electrolyte can be injected at an appropriate stage during the electrochemical device manufacturing process according to the manufacturing process and required performance of the final product. That is, the injection can be performed before assembling the electrochemical device or at the final stage of assembling the electrochemical device.
[0134] A separator may be additionally included between the positive electrode and the negative electrode.
[0135] The separator is capable of allowing lithium ions to be transported between the positive electrode and the negative electrode while isolating or isolating the positive electrode and the negative electrode from each other. Such a separator can be made of a porous, non-conductive or insulating material, and is not particularly limited as long as it is used as a separator in a conventional lithium secondary battery. The separator can be an independent component such as a membrane, or a coating added to the positive electrode and / or the negative electrode.
[0136] It is preferred that the separator has excellent wettability to the electrolyte and low resistance to ion migration of the electrolyte.
[0137] The separator may be made of a porous substrate. The porous substrate can be used as long as it is a porous substrate commonly used for secondary batteries, and may be composed of a porous polymer film alone or by laminating them, for example, a non-woven fabric or a polyolefin porous film made of glass fiber or polyethylene terephthalate fiber with a high melting point, but is not limited thereto.
[0138] The present invention has no particular limitation on the material of the porous substrate, and any material can be used as long as it is a porous substrate commonly used in electrochemical devices. For example, the porous substrate may include at least one material selected from the following: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyamide, polyacetal, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzophenone), ... azoles) and polyarylates.
[0139] The thickness of the porous substrate is not particularly limited, but may be 1 μm to 100 μm, preferably 5 μm to 50 μm. Although the thickness range of the porous substrate is not particularly limited to the above range, if the thickness is much thinner than the above lower limit, the mechanical properties deteriorate and thus the separator may be easily damaged during battery use.
[0140] The average size and porosity of pores present in the porous substrate are also not particularly limited, but may be 0.001 μm to 50 μm and 10% to 95%, respectively.
[0141] The lithium secondary battery according to the present invention can be manufactured through lamination, stacking, and folding processes of the separator and the electrodes in addition to a general winding process.
[0142] The shape of the lithium secondary battery is not particularly limited, and may be various shapes such as a cylindrical shape, a laminate shape, and a coin shape.
[0143] In addition, the present invention provides a battery module including the lithium-sulfur battery as a unit cell.
[0144] The battery module can be used as a power source for medium or large-sized devices requiring high temperature stability, long cycle characteristics, high capacity characteristics, and the like.
[0145] Examples of such medium to large devices may include, but are not limited to: power tools powered and moved by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems, etc.
[0146] Preferred Implementation
[0147] Hereinafter, in order to help understand the present invention, preferred embodiments of the present invention will be described. However, it will be apparent to those skilled in the art that the following examples are only used to illustrate the present invention, and that various changes and variants can be accomplished within the scope and spirit of the present invention, and such changes and variants are within the scope of the appended claims.
[0148] Examples and Comparative Examples
[0149] Example 1
[0150] The surface of the oxidized copper thin film was reduced and the copper surface was pre-faceted by flowing 300 sccm of argon and 50 sccm of hydrogen through a 20 μm thick copper current collector at a temperature of 1035° C. for 20 minutes. Thereafter, 20 sccm of methane gas was additionally injected at 1035° C. and chemical vapor deposition was performed at a roll-to-roll moving speed set at 6 m / hr to prepare a copper current collector in which a protective layer containing graphene with a thickness of 1.0 nm was formed on both sides.
[0151] Example 2
[0152] A lithium metal foil having a thickness of 45 μm was placed on one face of the copper current collector having the protective layer obtained in Example 1, and pressed with a roll press to prepare a negative electrode.
[0153] 90 wt % of sulfur-carbon composite material (S / C 7:3 by weight) as a positive active material, 5 wt % of Deko Black as a conductive material, and 5 wt % of styrene-butadiene rubber / carboxymethyl cellulose (SBR / CMC 7:3) were mixed to prepare a positive electrode slurry composition.
[0154] Then, the prepared positive electrode slurry composition was coated on an aluminum current collector, dried at 50° C. for 12 hours, and compressed with a roll press to prepare a positive electrode.
[0155] The prepared negative electrode and positive electrode were placed opposite to each other in a CR2032 coin cell, and a polyethylene separator with a thickness of 16 μm and a porosity of 68% was inserted between them, and then 70 μl of electrolyte was injected to fabricate a coin-type lithium-sulfur battery.
[0156] At this time, as an electrolyte, a mixed solution was used in which 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % lithium nitrate (LiNO3) were dissolved in an organic solvent composed of 1,3-dioxolane and dimethyl ether (DOL:DME=1:1 (volume ratio)).
[0157] Example 3
[0158] A pouch-type lithium-sulfur battery was prepared in the same manner as in Example 2 above, except that a negative electrode obtained by pressing a lithium metal foil of the same thickness on both faces of the copper current collector with a protective layer obtained in Example 1 was used, and a pouch-type battery in which 5 bicells were stacked was manufactured.
[0159] Example 4
[0160] A copper current collector having a 1.5 nm thick graphene-containing protective layer formed on both sides was manufactured in the same manner as in Example 1, except that the injection rate of methane gas was changed to 5 sccm and the roll-to-roll moving speed was changed to 1.5 m / hr during the chemical vapor deposition process.
[0161] Example 5
[0162] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector with a protective layer in Example 4 was used instead of that in Example 1.
[0163] Example 6
[0164] A copper current collector in which a 35 nm thick graphene-containing protective layer was formed on both sides was manufactured in the same manner as in Example 1, except that the injection rate of hydrogen gas was changed to 25 sccm during chemical vapor deposition.
[0165] Example 7
[0166] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector with a protective layer in Example 6 was used instead of that in Example 1.
[0167] Example 8
[0168] A copper current collector in which a 20 nm thick graphene-containing protective layer was formed on both sides was manufactured in the same manner as in Example 1, except that the injection rate of hydrogen gas was changed to 35 sccm during chemical vapor deposition.
[0169] Example 9
[0170] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector with a protective layer in Example 8 was used instead of that in Example 1.
[0171] Comparative Example 1
[0172] As a copper current collector, a copper thin film having a thickness of 20 μm without forming a protective layer was prepared.
[0173] Comparative Example 2
[0174] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector of Comparative Example 1 was used instead of that of Example 1.
[0175] Comparative Example 3
[0176] A pouch-type lithium-sulfur battery was prepared in the same manner as in Example 3 above, except that the copper current collector of Comparative Example 1 was used instead of that of Example 1.
[0177] Comparative Example 4
[0178] A slurry composition was prepared by mixing 95 wt% of exfoliated graphene powder (product from G3) and 5 wt% of styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC 7:3).
[0179] Then, the prepared slurry composition was coated on both surfaces of a copper current collector having a thickness of 20 μm, dried at 60° C. for 12 hours, and compressed with a roller press to prepare a copper current collector coated with an exfoliated graphene protective layer.
[0180] Comparative Example 5
[0181] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector of Comparative Example 4 was used instead of that of Example 1.
[0182] Comparative Example 6
[0183] A copper current collector in which a 100 nm-thick graphene-containing protective layer was formed on both faces was manufactured in the same manner as in Example 1, except that the injection rate of hydrogen gas was changed to 5 sccm during chemical vapor deposition.
[0184] Comparative Example 7
[0185] A coin-type lithium-sulfur battery was manufactured in the same manner as in Example 2 above, except that the copper current collector of Comparative Example 6 was used instead of that of Example 1.
[0186] Experimental Example 1. Scanning Electron Microscope Analysis
[0187] The surfaces of the copper current collectors with protective layers prepared in Example 1 and Comparative Example 1 were observed with a scanning electron microscope (SEM). As a scanning electron microscope, JSM7610F manufactured by JEOL was used. The results obtained at this time are shown in FIG. Figure 1 and 2 middle.
[0188] It can be seen that reference Figure 2 , the surface of Comparative Example 1 has a surface structure in which nanometer-scale copper crystals are clustered together, but Figure 1 As shown, the surface of Example 1 is a single layer and has a smooth surface because a graphene-containing protective layer with fewer defects is formed.
[0189] Experimental Example 2. X-ray Photoelectron Spectroscopy and Raman Spectroscopy Analysis
[0190] (1) Antioxidation properties of the protective layer and the size of graphene grains
[0191] After the copper current collectors with the protective layer prepared in Examples 1 and 4 were subjected to an artificial thermal oxidation reaction at 200° C. for 6 hours, the oxidation degree of copper was measured using an X-ray photoelectron spectrometer.
[0192] After measuring the degree of copper oxidation, the surfaces of the copper current collectors of Examples 1 and 4 were measured with a scanning electron microscope, and the size of the graphene grains was measured by analyzing them. The results obtained at this time are shown in Tables 1 and 2 and Figure 3 middle.
[0193] Table 1:
[0194]
[0195] Table 2:
[0196] Example 1 Example 4 <![CDATA[The size of the graphene grains (μm 2 )]]> 110 440
[0197] Refer to Tables 1 and 2 and Figure 3 It can be confirmed that, in the case of Example 4, the grain size of graphene contained in the protective layer is about 4 times that of Example 1, whereby grain boundaries (ie, defects that can serve as a cause of corrosion) are reduced and oxidation resistance can be improved.
[0198] It can be seen from these results that the fewer defects and the larger the grain size of the graphene contained in the protective layer, the better the resistance to permeation of lithium polysulfide.
[0199] (2) Analysis of the structure and defects of graphene contained in the protective layer
[0200] The graphene of the protective layer prepared according to Examples 1, 4 and 6 and Comparative Examples 1 and 4 was subjected to Raman spectroscopy analysis using a Raman spectrometer (Raman-XploRA, HORIBA Scientific). In addition, the cross section of the copper current collector with the protective layer prepared in Example 6 was observed with a scanning electron microscope (SEM). As a scanning electron microscope, JSM7610F manufactured by JEOL was used. The results obtained at this time are shown in Tables 3 and 4. Figure 4 middle.
[0201] Table 3:
[0202] <![CDATA[D peak / G peak (I D / I G )]]> <![CDATA[2D peak / G peak (I 2D / I G )]]> Example 1 0.09 1.1 Example 4 0.02 1.2 Example 6 0.12 0.2 Comparative Example 1 - - Comparative Example 4 0.9 0.2 G3's exfoliated graphene powder 1.00 0.02
[0203] As shown in Table 3 above, it can be seen that, as a result of Raman spectroscopy, in the case of graphene contained in the protective layer according to Examples 1, 4 and 6, the ratio of the D peak to the G peak is significantly lower than that of the graphene contained in the protective layer according to Comparative Example 4, thereby forming graphene with fewer defects on the negative electrode collector by chemical vapor deposition.
[0204] In addition, it can be confirmed that in the case of Examples 1 and 4, since the ratio of the 2D peak to the G peak is higher than that of Example 6, multilayer graphene is formed in the case of Example 6. Specifically, referring to Figure 4 In the case of Example 6, it can be seen that graphene having a multilayer structure in which the thickness of the protective layer was at the level of 30 nm was prepared.
[0205] Experimental Example 3. Evaluation of battery life characteristics
[0206] The life characteristics of the lithium-sulfur batteries manufactured in Examples 2, 3, 5, 7 and 9 and Comparative Examples 2, 3, 5 and 7 were evaluated.
[0207] Specifically, in Examples 2, 5, 7 and 9 and Comparative Examples 2, 5 and 7, after repeated discharge and charge at a current density of 0.1C for 3 times at 25°C, and then discharged and charged for 3 times at a current density of 0.2C, the discharge capacity and coulombic efficiency were measured while performing 0.5C discharge and 0.3C charge to evaluate the life characteristics of the battery. The results obtained at this time are shown in Figure 5 and 6 middle.
[0208] In addition, in Example 3 and Comparative Example 3, after discharging and charging were repeated 3 times at 25°C with a current density of 0.1C, the discharge capacity and coulombic efficiency were measured while performing 0.3C discharge and 0.2C charge to evaluate the life characteristics of the battery. The results obtained at this time are shown in Figure 7 middle.
[0209] In addition, the batteries of Example 3 and Comparative Example 3 were operated for 117 cycles and then disassembled, and the cross-section of the negative electrode was observed using a scanning electron microscope (SEM). The results obtained at this time are shown in Figure 8 and 9 middle.
[0210] pass Figures 5 to 7 It can be seen that the battery according to the embodiment has more excellent life characteristics than the comparative example.
[0211] Specifically, it can be seen that compared with Comparative Examples 2 and 3 including negative electrode collectors that do not include a protective layer, in the case of the batteries of Examples 2, 3, 5, 7 and 9 (which include: negative electrode collectors including a graphene protective layer), the coulombic efficiency retention rate and capacity retention rate are higher during the cycle.
[0212] In addition, refer to Figure 7 It can be seen that, compared with Comparative Example 3, the life of Example 3 is increased by about 17.3%.
[0213] In addition, if Figure 6 As shown, it can be seen that, compared with Example 7, in Comparative Example 5, in which the protective layer is formed by coating a composition containing exfoliated graphene rather than by chemical vapor deposition, there are many defects in the graphene contained in the protective layer, so that the life characteristics of the battery are significantly lower.
[0214] In addition, if Figure 8 and 9 As shown, it can be seen that, compared with Example 3, in the case of Comparative Example 3, the current collector becomes porous due to the reaction with lithium polysulfide, and a large amount of sulfide-based by-products are also generated.
[0215] From these results, it can be confirmed that when the negative electrode according to the present invention is included, the life characteristics of the lithium-sulfur battery are improved by including a protective layer containing graphene with fewer defects and thereby suppressing corrosion of the negative electrode current collector caused by lithium polysulfide.
Claims
1. A negative electrode for a lithium-sulfur battery, the negative electrode for a lithium-sulfur battery comprising: a negative electrode current collector, and a protective layer, the protective layer being located on at least one surface of the negative electrode current collector and containing graphene, The graphene has a ratio of D peak to G peak of 0.01 to 0.6 in a Raman spectrum. 2 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the protective layer comprises a single-layer graphene or a multi-layer graphene. 3 . The negative electrode for a lithium-sulfur battery according to claim 2 , wherein the multilayer graphene has 2 to 100 layers. 4 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the graphene has a ratio of a 2D peak to a G peak of 0.2 to 2.0 in a Raman spectrum. 5 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the protective layer has a thickness of 0.1 nm to 50 nm. 6 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the protective layer is impermeable to lithium polysulfide. 7 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the protective layer is formed by chemical vapor deposition.
8. The negative electrode for a lithium-sulfur battery according to claim 1, wherein the negative electrode current collector comprises at least one selected from the group consisting of nickel, copper, stainless steel, titanium, vanadium, chromium, manganese, iron, cobalt, zinc, molybdenum, tungsten, silver, gold, ruthenium, platinum, iridium, aluminum, tin, bismuth and antimony. 9 . The negative electrode for a lithium-sulfur battery according to claim 1 , wherein the negative electrode current collector is in the form of a film, a sheet, a foil, a screen, a mesh, a porous body, a foam or a non-woven fabric. 10 . The negative electrode for a lithium-sulfur battery according to claim 1 , further comprising a negative electrode active material layer on the protective layer. 11 . The negative electrode for a lithium-sulfur battery according to claim 10 , wherein the negative electrode active material layer comprises lithium metal or a lithium alloy. 12 . The negative electrode for a lithium-sulfur battery according to claim 10 , wherein the negative electrode active material layer comprises a lithium metal thin film.
13. A lithium-sulfur battery, comprising: a positive electrode, the positive electrode comprising a positive electrode active material; The negative electrode for a lithium-sulfur battery according to claim 1; and Electrolytes.
14. The lithium-sulfur battery according to claim 13, wherein the positive electrode active material comprises at least one selected from the group consisting of elemental sulfur S8; Li2S n , wherein n ≥ 1; and organic sulfur compounds.
